The Association Between Some Endocrine Conditions and COVID-19: A Review - Harem Othman Smail (Biology, Medicine, & Natural Product Chemistry, 2023)
The review aimed to understand and explain the association between some major endocrine conditions and COVID-19. Since March 2019, COVID-19 has been identified as a pandemic by the World Health Organization (WHO) and has infected millions of individuals worldwide. According to the literature review, endocrine disorders include diabetes, obesity, hypertension, and thyroid. The development and progress of COVID-19 patients could be affected but not yet approved by all the studies. In diabetes mellitus, COVID-19 may affect cytokines and increase releases of IL-1, IL-6, and complications caused by diabetes. In obese patients, there was an increased risk of progressing to severe COVID-19. Because of the international spread of severe acute respiratory syndrome coronavirus, clinicians should pay special attention to obese patients who should be monitored closely with timely and aggressive care. COVID-19 pathophysiology and risk in a high incidence of hypertension has been found in patients with COVID-19 and can be studied in many kinds of studies, such as in China. However, hypertension is considered one of the most significant risk factors for COVID-19. In addition to the above data on associations between COVID-19 and endocrine disorders, data on thyroid function or thyroid disease in COVID-19 is not yet available and cannot be commonly reported.